Law Enforcement Against Unfair Competition Among Notaries According to Notary Ethics Code - Asranita; Siti Malikhatun Badriyah (LEGAL BRIEF, 2022)
Notary is a public office who is authorized to make authentic deeds which have perfect verification power. In performing their profession and/or duties, notaries must obey and be attached and oriented to the existed rules, they are Constitution No 30 Year 2004 About Notary Office, Constitution No 2 Year 2014 About Amendment of Constitution No 30 Year 2004 About Notary Office (which is then called UUJN) and Notary Ethics Code. This research aimed to find out how law enforcement against unfair competition among notaries according to Notary Ethics Code is and what the legal effects to Notaries who are involved in an unfair competition are. This research was done by applying descriptive qualitative method sourced from literature review and previous studies. From this research, it was found that the law enforcement against unfair competition among notaries which is included in Notary ethics code violation is contained in the Notary Ethics Code. In a case of a Notary involved in an unfair competition is definitely violate the existed ethics code and can raise a legal effect which is given a sanction.